Community structure of coral reefs in Pulau Mertang, Johor, Malaysia - Mohamad Saupi Ismail; Khoo, Mei Ling (Penerbit Universiti Kebangsaan Malaysia, 2019)
A study was conducted at nine sites around Pulau Mertang using point intercept transect method to determine the coral community of the islands. The results showed the reefs around Pulau Mertang were in good condition with an average live coral cover of 51.0 + 2.35%, which is higher than the average live coral cover for Malaysia (42.5%). Hard corals were found monopolizing the benthic fauna along all transects. A total of 25 different genera from 12 families of scleractinian coral were observed during this survey. The dominant genera found at Pulau Mertang are Acropora (41.26 + 20.88%) and Montipora (14.24 + 21.57%), while other sessile life form was dominated by zoanthids (7.59 + 11.92%). The percentage cover of the abiotic component of transect was dominated by dead corals (15.19 + 2.26%). Coral genus diversity was highest at Pulau Mertang Barat (H’ = 2.24), followed by Pulau Mertang Timur (H’ =1.71) and Pulau Mertang Tengah (H’=1.56). Most reefs in Pulau Mertang are classified as C4 categories and all islands show low values of mortality index (MI = 0.23). High coral live cover, diversity (H’), conservation class (C4) and low mortality index and domination by branching and tabular Acropora are attributes of a healthy reef. Therefore, it is concluded that the reefs around Pulau Mertang were still in good condition and healthy. From an ecological point of view, it is the closest representation of an undisturbed reef of a non-marine park island in Johor. Thus, this study forms an initial step in understanding the reef community and provides a basis for future observations on the marine ecosystem of Pulau Mertang.